In vitro percutaneous absorption and metabolism of ozenoxacin in excised human skin. (August 2014) - Santos, Benjamin; Ortiz, Jordi; Gropper, Savion
ABSTRACT: : In vitro studies using excised human skin samples were conducted to evaluate the percutaneous absorption and skin metabolism of ozenoxacin. The formulations studied were 1% ointment, 1% cream and 2% cream. Permeation assays met the conditions for infinite dose experiments. In all but one case, ozenoxacin concentrations in receptor fluid samples of Franz diffusion cells were below the limits of quantification (0.04 μg/ml) by liquid chromatography/mass spectrometry/electrospray ionization at the designated time points. Across all four absorption studies, ≤0.015% of the applied ozenoxacin dose permeated through the skin over the course of 24 or 48 h. Ethnic origin had no influence on absorption. Ozenoxacin at concentrations of 7, 35 and 70 μM was metabolically stable in the presence of freshly prepared human skin discs.